INDICATORS OF THE PRACTICE OF POWER IN LANGUAGE CLASSROOMS (TEFLIN, 2011)
Abstract: This paper attempts to reveal some strategies performed by teacher which indicate that s/he is exercising power in managing and con-ducting language teaching and learning process. Such power may be maniÂfested in terms of the frequency of directives or of the holding of control over the interaction Process. Despite the fact that exercising power seems to impair justice, democracy, and humanity because it implies inequality, in a pedagogical context, especially in a language teaching and learning process, such a practice may still be beneficial and justifiable. Among the benefits of the exercise of power are enumerated by the end of the paper.